ANALISIS PENGARUH KUALITAS KEHIDUPAN KERJA (QUALITY OF WORK LIFE) DAN IKLIM KERJA TERHADAP LOYALITAS KERJA DENGAN KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING PADA PT SURVEYOR INDONESIA CABANG PALEMBANG - Octavia, Dahlia (Program Studi Manajemen Fakultas Ekonomi Universitas Palembang, 2019)
The purpose of this study was to determine the effect of quality of work life and work climate on work loyalty with job satisfaction as an intervening variable at PT Surveyor Indonesia Palembang Branch. The study was conducted on employees of PT Surveyor Indonesia Palembang Branch with 49 respondents. Research respondents are all employees except the leadership level. Data collection was carried out by distributing questionnaires using a Likert scale. The data analysis technique used is Structural Equation Modeling (SEM) with Partial Least Square (PLS) approach. The results of this study revealed that the quality of work life and work climate affect work satisfaction, job satisfaction has a positive and significant effect on work loyalty, quality of work life and work climate have a positive and significant effect on work loyalty.